Solution of Navier-Stokes equations by fourth-order compact schemes and AUSM flux splitting - Mawlood, M.K.; Basri, S.; Asrar, Waqar; Omar, Ashraf Ali; Mokhtar, A.S.; Ahmad, M.M. (Emerald Group Publishing Limited, 2006)
Purpose – To develop a high-order compact finite-difference method for solving flow problems containing shock waves. Design/methodology/approach – A numerical algorithm based on high-order compact finite-difference schemes is developed for solving Navier-Stokes equations in two-dimensional space. The convective flux terms are discretized by using advection upstream splitting method (AUSM). The developed method is then used to compute some example laminar flow problems. The problems considered have a range of Mach number that corresponds to subsonic incompressible flow to hypersonic compressible flows that contain shock waves and shock/boundary-layer interaction.